2015
DOI: 10.1590/bjpt-rbf.2014.0124
|View full text |Cite
|
Sign up to set email alerts
|

Interval training based on ventilatory anaerobic threshold increases cardiac vagal modulation and decreases high-sensitivity c-reative protein: randomized clinical trial in coronary artery disease

Abstract: Background: Autonomic dysfunction and inflammatory activity are involved in the development and progression of coronary artery disease (CAD), and exercise training has been shown to confer a cardiovascular benefit. Objective: To evaluate the effects that interval training (IT) based on ventilatory anaerobic threshold (VAT) has on heart rate variability (HRV) and high-sensitivity C-reactive protein (hs-CRP) levels, as well as the relationship between both levels, in patients with CAD and/or cardiovascular risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…VAT has been considered a physiological parameter internationally accepted for assessing the aerobic functional capacity and quantifying aerobic exercise intensity 19 . In addition, some authors have reported the importance of physical training at levels close to VAT 8 .…”
Section: Discussionmentioning
confidence: 99%
“…VAT has been considered a physiological parameter internationally accepted for assessing the aerobic functional capacity and quantifying aerobic exercise intensity 19 . In addition, some authors have reported the importance of physical training at levels close to VAT 8 .…”
Section: Discussionmentioning
confidence: 99%
“…However, different effects of physical activity depending on age, gender, race and health status were highlighted. [9,26]. Most studies apply to persons who are overweight or obese and also with underlying metabolic disorders and/ or cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, strategies that can act positively on autonomic modulation, such as physical exercise (12)(13)(14) should be studied in subjects with Mets to reduce cardiovascular risk in this population. In healthy subjects or those with pathological conditions, aerobic interval training (AIT) has been highlighted for its easy applicability and positive effects that include increases in parasympathetic autonomic modulation and global variability (13,15,16), however, to our knowledge, there are no studies that evaluated the effects of this type of intervention on autonomic behavior in subjects with Mets.…”
Section: Introductionmentioning
confidence: 99%